2018
DOI: 10.1016/j.jpowsour.2017.11.060
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical behavior of poly 1-pyrenemethyl methacrylate binder and its effect on the interfacial chemistry of a silicon electrode

Abstract: The physico-chemical properties of poly (1-pyrenemethyl methacrylate) (PPy) are presented with respect to its use as a binder in a Si composite anode for Li-ion batteries. PPy thin-films on Si(100) wafer and Cu model electrodes are shown to exhibit superior adhesion as compared to conventional polyvinylidene difluoride (PVdF) binder. Electrochemical testing of the model bi-layer PPy/Si(100) electrodes in a standard organic carbonate electrolyte reveal higher electrolyte reduction current and an overall irrever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…For example, an electrolyte decomposition product (LiF) was observed to be present in lesser quantities on the 110 face, when compared to the other crystalline faces. A similar study was performed at the Si (100) surface by Haregewoin et al, where they found the coverage of a 25 nm-thick binder has a selective influence of solvent transport properties, which alters the interfacial process formed at the Si surface . CV was also used to probe the electrochemical accessibility of surface-modified electrodes.…”
Section: Classical Electrochemistry For Materials Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…For example, an electrolyte decomposition product (LiF) was observed to be present in lesser quantities on the 110 face, when compared to the other crystalline faces. A similar study was performed at the Si (100) surface by Haregewoin et al, where they found the coverage of a 25 nm-thick binder has a selective influence of solvent transport properties, which alters the interfacial process formed at the Si surface . CV was also used to probe the electrochemical accessibility of surface-modified electrodes.…”
Section: Classical Electrochemistry For Materials Analysismentioning
confidence: 83%
“…A similar study was performed at the Si (100) surface by Haregewoin et al, where they found the coverage of a 25 nm-thick binder has a selective influence of solvent transport properties, which alters the interfacial process formed at the Si surface. 33 CV was also used to probe the electrochemical accessibility of surface-modified electrodes. Nicolau et al demonstrated that alkylphosphonic acid selfassembled monolayers (SAMs) controlled the wettability of solvent at the LiMn 2 O 4 cathode surface, which influenced the molecule and ion mobility at the vicinity of the electrode.…”
Section: Potentiostatic Intermittentmentioning
confidence: 99%
“…during their slurry preparation . This same work showed zeta potential measurements (though the procedure was not reported which is important as the zeta potential measurements are sensitive to concentrations, salts, and equilibration time amongst others) . In the Delpuech et al .…”
Section: Figurementioning
confidence: 97%
“…There have been numerous studies reporting or exploring the role of the binder . Most of these studies focus on the use of a single binder with a single silicon source that then are subjected to different drying schemes, voltage ranges, cycle number, processing conditions . Others focus on the same base binder with chemical modifications to the backbone or chemical structure or ratio of components .…”
Section: Figurementioning
confidence: 99%
“…The conducting polymer polypyrrole has been widely used in energy storage devices such as batteries and supercapacitors, usually as a binder and conductive additive [176] . Studies have found that the polymer can form a conductive matrix that provides a conductive skeleton to the cell, and it can also be used as a host matrix to prevent large volume changes during charge/discharge cycles [177] .…”
Section: Conducting Polymers Coating Layermentioning
confidence: 99%